A IMPLEMENTATION OF THE STRENGTHENING PANCASILA STUDENT PROFILE PROJECT IN THE ISLAMIC RELIGIOUS EDUCATION AND CHARACTER (PAI-BP) SUBJECT AT SMA 2 PLUS PANYABUNGAN - Zainul Arifin; Nabilah Lubis; Irma Suryani Siregar; Suryadi (Journal International Inspire Education Technology, 2025)
This study discusses the implementation of the Strengthening Pancasila Student Profile Project (P5) in the Islamic Religious Education and Character (PAI-BP) subject at SMA 2 Plus Panyabungan. The research focuses on describing the application of the P5 project in PAI-BP learning. This study employed a qualitative approach, with data collection techniques including observation, interviews, and documentation. The findings reveal that PAI-BP teachers developed contextual teaching modules using the theme “Build Their Soul and Body” through issues such as bullying, which were linked to Islamic values. The school also provided support for the project’s implementation. As a result, the project has begun to foster students’ awareness of religious values and character traits such as empathy and social care. However, the project’s implementation still requires improvement, particularly regarding school policy, scheduling, teacher training, and sustainable character building to optimally achieve the goal of forming the Pancasila student profile. The novelty of this research lies in connecting the contextual issue of bullying with the PAI-BP subject, positioning Islamic values as a practical solution to ethical problems faced by students. Nonetheless, the findings also indicate that the P5 integration process has not yet run optimally.